Perceived underqualification and job attitudes: the role of transformational leadership. Issue 8 (6th September 2018) - Sim, Yerim; Lee, Eun-Suk
Abstract : Purpose: The purpose of this paper is to delve into perceived underqualification, which refers to employees' awareness that they have deficient abilities relative to their job demands (abilities<demands). In examining person–job (P–J) misfit, previous research has primarily focused on one type of misfit, overqualification (abilities>demands), leaving the other type, underqualification, unexplored. To address the neglect, this study investigates how perceived underqualification relates to job attitudes (job satisfaction, organizational commitment, and turnover intention) and how transformational leadership moderates the relationships. Design/methodology/approach: Survey data were collected from employees working at diverse organizations in South Korea over two waves; at Time 1, perceived underqualification and transformational leadership were measured and at Time 2, job attitude variables were measured. Responses from 188 employees were used for hypothesis testing. Findings: Perceived underqualification is negatively related to job satisfaction and organizational commitment and positively related to turnover intention when transformational leadership is low. However, under high transformational leadership, such negative attitudinal implications of perceived underqualification are weakened. Originality/value: By examining underqualification for the first time, this study corrects the current incomplete and biased understanding of P–J misfit, which is exclusively overqualification-focused. In addition, this study provides new insight into individual responses to P–J misfit by revealing that the responses are not always negative. This study specifies transformational leadership as the contingency factor that enables such responses, thus further advancing the P–J misfit literature that has hardly examined the leadership effect.